Distinguishing Majorana and quasi-Majorana bound states in a hybrid superconductor-semiconductor nanowire with inhomogeneous potential barriers - Hongyu Tian (Results in Physics, 2021)
A semiconductor-superconductor hybrid nanowire with a spatially inhomogeneous potential can host partially separated quasi-Majorana bound states (quasi-MBSs). In this work, we consider a two-lead (three-terminal) setup of transport with two different potential barriers and find that for a Majorana nanowire with smooth potential barriers at both ends, the quasi-MBSs can be well-separated at the nanowire’s endpoints just like true MBSs, and the nonlocal conductance process displays parity-related interference behavior in both the quasi-MBS regime and topological regime. By contrast, for a Majorana nanowire with a smooth potential barrier only at one end, the quasi-MBSs are partially separated, and no parity-related interference pattern occurs in the quasi-MBS regime. Our findings provide a simple way to distinguish MBSs from quasi-MBSs and give some insight into quasi-MBS-based quantum computation.